Modulation of hyaluronan synthases and involvement of T cell-derived hyaluronan in autoimmune responses to transplanted islets - John A. Gebe; Michel D. Gooden; Gail Workman; Nadine Nagy; Paul L. Bollyky; Thomas N. Wight; Robert B. Vernon (Matrix Biology Plus, 2021)
The extracellular matrix glycosaminoglycan hyaluronan (HA) accumulates in human and mouse islets during the onset of autoimmune type 1 diabetes (T1D). HA plays a critical role in T1D pathogenesis, as spontaneous disease is blocked in mice fed the HA synthesis inhibitor 4-methylumbelliferone (4MU). The present study demonstrates the involvement of HA in T cell-mediated autoimmune responses to transplanted islets and in in vivo and in vitro T cell activation. Scaffolded islet implants (SIs) loaded with RIP-mOVA mouse islets expressing chicken ovalbumin (OVA) on their β cells were grafted into T and B cell-deficient RIP-mOVA mice, which subsequently received CD4+ T cells from DO11.10 transgenic mice bearing OVA peptide-specific T cell receptors (TcRs), followed by injection of OVA peptide to induce an immune response to the OVA-expressing islets. By affinity histochemistry (AHC), HA was greatly increased in grafted islets with T cell infiltrates (compared to islets grafted into mice lacking T cells) and a portion of this HA co-localized with the infiltrating T cells. Transferred T cells underwent HA synthase (HAS) isoform switching – T cells isolated from the SI grafts strongly upregulated HAS1 and HAS2 mRNAs and downregulated HAS3 mRNA, in contrast to T cells from graft-draining mesenteric lymph nodes, which expressed HAS3 mRNA only. Expression of HAS1 and HAS2 proteins by T cells in SI infiltrates was confirmed by immunohistochemistry (IHC). DO11.10 mice fed 4MU had suppressed in vivo T cell immune priming (measured as a reduced recall response to OVA peptide) compared to T cells from control mice fed a normal diet. In co-cultures of naïve DO11.10 T cells and OVA peptide-loaded antigen-presenting cells (APCs), pre-exposure of the T cells (but not pre-exposure of APCs) to 4MU inhibited early T cell activation (CD69 expression). In addition, T cells exposed to 4MU during activation in vitro with anti-CD3/CD28 antibodies had inhibited phosphorylation of the CD3ζ subunit of the TcR, a very early event in TcR signaling. Collectively, our results demonstrate that T cell-derived HA plays a significant role in T cell immune responses, and that expression of T cell HAS isoforms changes in a locale-specific manner during in vivo priming and functional phases of the T cell response.